Consuming Fat Supplemented Diet with Different Vegetable Oils Impacts the Serum Lipid Profiles and Body Weights of Male Rats - Mahitab H. El Bishbishy; Nora M. Aborehab (European Scientific Journal, ESJ, 2018)
This research was conducted in order to evaluate the influence of consuming diet supplemented with different types of fixed oils (Olive oil, Soybean oil and Coconut oil) on the lipid profiles and body weights of healthy albino rats and linking these effects to their chemical compositions thus reaching out to recommendation about the healthiest type of fats among the studied oils to be used in healthy nutrition programs. The lipid contents of the fixed oils were determined by Gas Chromatography (GC) method, the vitamin contents were determined by High Performance Liquid Chromatography (HPLC) and the proximate analyses of the oils were also evaluated by different assays. Twenty-four healthy male albino rats were divided into four groups as follows: Olive oil supplemented diet, Soybean oil supplemented diet, Coconut oil supplemented diet and oil-free supplemented diet control group. The dieting continued for 28 days, at the end of which, the serum levels of total cholesterol, Low Density Lipoproteins (LDL), High Density Lipoproteins (HDL), Triglycerides (TG) and Free Fatty Acid (FFA) were measured spectrophotometrically and the rats body weights were monitored on daily basis. The results showed that olive oil, the richest studied oil in unsaturated fatty acids (84.16 %), had favorable effect on the rats’ lipid profiles, serum free fatty acid levels and rats body weights. In conclusion, olive oil supplemented diets are considered healthy diets and beneficial to decrease the risk of cardiovascular diseases.